Pharmacotherapy of alcoholism – an update on approved and off-label medications. (13th August 2017) - Soyka, Michael; Müller, Christian A.
ABSTRACT: Introduction : Only a few medications are available for the treatment of alcohol use disorders (AUDs). Areas covered : This paper discusses approved AUD medications, including the opioid antagonists naltrexone and nalmefene (the latter is licensed for reduction of alcohol consumption only), the putative glutamate receptor antagonist acamprosate and the aldehyde dehydrogenase inhibitor disulfiram. It also covers off-label medications of interest, including topiramate, gabapentin, ondansetron, varenicline, baclofen, sodium oxybate and antidepressants. Clinical implications, benefits and risks of treatment are discussed. Expert opinion : Acamprosate, naltrexone, nalmefene and disulfiram are the only approved 'alcohol-specific' drugs. Acamprosate and naltrexone have been evaluated in numerous clinical trials and represent evidence-based treatments in AUDs. Nalmefene use, however, is controversial. Supervised disulfiram is a second-line treatment approach. Compounds developed and licensed for different neuropsychiatric disorders are potential alternatives. Encouraging results have been reported for topiramate, gabapentin and also varenicline, which might be useful in patients with comorbid nicotine dependence. The GABA (γ-aminobutyric acid)-B receptor agonist baclofen has shown mixed results; it is currently licensed for the treatment of AUDs in France only. Gabapentin may be close to approval in the USA. Further studies of these novel treatment approaches in AUDs are needed.